Participation ahead : Perceptions of Masters degree students on Reciprocal Peer Learning Activities - Lelis, Catarina (Journal of learning design, 2017)
Peer Learning is broadly described as the development of knowledge or skills by individuals from similar statutory conditions who are learning from and with each other in both formal and informal ways. There is a considerable amount of published work on peer learning in the context of schools and undergraduate courses but little work has been developed around postgraduate levels, specifically with Masters courses. The goal of the research presented in this paper was to understand how Masters degree students perceive and engage with a peer learning activity set in a taught module. One specialist subject topic from the curriculum was assigned to each student who, during two sessions in regular teaching times, had to perform both as peer tutor and tutee in a reciprocal peer learning approach. Two questionnaires were applied - one for each role the students had to perform. Results reveal that the majority of students considered the peer tutor role undeniably positive; however, while performing as tutees, students expressed skepticism regarding the effectiveness of the approach. As the credibility of peers was evidenced as an issue (when set against these students' high expectations), this paper contends that reciprocal peer learning may not be the most suitable peer learning method for master levels. [Author abstract]